Prototype of Monitoring and Controlling System on Gondola Cage Security Based Android Application - Dionova, Brainvendra Widi; Junesco Vresdian, Devan; Ananda Hapsari, Anindya; Budi Priyono, Sigit; Haryudiniarti, Ayu Nurul; Nafiulana Tri, Anggita; Manfaluthy, Mauludy; N. Abdulrazaq, Mohammed (Eksergi, 2022)
Gondola is one of the facilities used in high-rise buildings that are used to access the outside of the building. Gondola has a maximum load limit that is safe to transport it. Gondola is also often damaged in the cage caused by collisions on the side of the building. Until now, the gondola control still uses buttons which also often experience problems. This study aims to provide monitoring of the cage load and provide information about the distance of the cage to surrounding objects. Gondola control through an android application also includes this research in order to provide an alternative if the buttons on the gondola control experience problems. The short-term goal of this research is to carry out an innovation in the gondola field by conducting experiments through prototypes. The medium term goal is to apply the results of this research into a gondola. The results of this study control and monitoring can function properly even though the results produced are not yet accurate due to the imperfect quality of components, materials and assembly.